PELAKSANAAN EKSEKUSI DI ATAS HAK PENGELOLAAN (HPL) NO. 3 MILIK PT. KAWASAN INDUSTRI MEDAN (Persero) (Studi Kasus Putusan PK No. 94 PK/PDT/2004) - ROSDIANA SARI MAHARANI (PREMISE LAW JURNAL, 2014)
ABSTRACT Execution as a legal action done by the Court to the loser in a certain case is a regulation and follow-up procedure from the process of a hearing. The objective of the research was to know whether judge’s consideration in the ruling of PK No. 94 PK/PDT/2004 has been in line with material law, to know how about the implementation of the execution of the Ruling of PK No. 94 PK/PDT/2004 was carried out on the Supervision Rights (HPL) No. 3, owned by PT Kawasan Industri Medan (Incorporated), and to know what legal remedy done by PT Kawasan Industri Medan (Incorporated) on the Judicial Review. Legal consideration for judges in giving the Ruling No. 94 PK/PDT/2004 has final and conclusive; but, in practice it cannot be carried out because at the time the establishment of the facts is done, it is different from the Ruling of PK. One of the attempts made by PT Kawasan Industri Medan (Incorporated) about the land boundary is by making a request for judge’s  decision in the District Court on the non-executable execution. Keywords: Execution, Supervision Rights (HPL)